Consumer behavior in the economy - Andrei Mihai Cristea; Oana Camelia Iacob; Dan Gabriel Cristea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
This paper aims to carry out an analysis of the disparities between urban and rural economic environment in Romania, which have negative effects over time for the entire country. The key imbalances between the two areas will be identified and a chronological analysis of figures obtained from the two areas over the years will be presented. A comparative analysis of urban / rural consumption behavior of households in the period 2005-2012 is showcased. The rural population is still heavily dependent on agriculture, while consumption characteristics are specific to relatively poor populations. Reducing disparities between urban and rural incomes and improvement of the quality of household consumption are priorities in regional development policy.
Keywords: 330; sustainable consumption; economic growth; consumerism interdependence; economic disparities